Civil Society Participation in Efforts to Prevent the Spread COVID-19 - Khusnul Prasetyo; Lukman Arif (Jurnal Administrasi Publik (Public Administration Journal), 2021)
This study aims to describe civil society participation in efforts to prevent the spread of COVID-19 in Sidoklumpuk Village, Sidoarjo Sub-District, Sidoarjo Regency and the obstacles faced. The method used was descriptive qualitative with data collection techniques through interviews, observation, documentation, and literature review. The results of this study indicate that civil society participation was carried out in mutual cooperation which was divided into four task forces including the Wani Ngandani Task Force which tried to educate residents to implement health protocols, while the Wani Jogo Task Force was tasked with limiting the mobility of residents with a one gate system. There was also the Wani Sehat Task Force which functions to ensure the availability of a place to wash hands in front of the house and a Wani Sejahtera Task Force which identified the food needs of Probable (ODP), Confirmation (PDP), Suspect (OTG) patients, and confirms outpatient care with predetermined criteria. Several obstacles were encountered such as lack of funds and low public awareness. The formation of Kampung Tangguh Semeru through the COVID-19 Prevention Task Force in Sidoklumpuk Village was a concrete form of civil society participation at the grassroots level with a partnership model.